2017
DOI: 10.24265/horizmed.2017.v17n2.06
|View full text |Cite
|
Sign up to set email alerts
|

Características de los factores de riesgo cardiovascular en una población urbana y rural de la selva peruana, julio - 2014

Abstract: RESUMENObjetivo: Evaluar la factibilidad de realizar una estratificación hemodinámica en pacientes con infarto agudo de miocardio con segmento ST elevado, mediante el uso de ecocardiografía transtorácica. Materiales y métodos: Estudio descriptivo, prospectivo y transversal que incorporó a 30 pacientes en ritmo sinusal con diagnóstico de infarto agudo de miocardio con ST elevado, ingresados a la unidad coronaria del Hospital Edgardo Rebagliati Martins. Se estimó: gasto cardíaco, presión de llenado de ventrículo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
1
0
2
Order By: Relevance
“…Our study showed that the highest proportion of individuals overweight belong to the urban population. These results coincide with an investigation carried out in Peru where 47.4% and 19.1% of the participants were overweight and obese respectively [ 39 ]; in Mexico, there is a record of 45% obesity in rural areas and 48% in urban areas [ 36 ], and in Venezuela it was evidenced that 60% of both populations are obese and overweight [ 40 ]. This variable is highly influenced by the lifestyle and customs of the two populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study showed that the highest proportion of individuals overweight belong to the urban population. These results coincide with an investigation carried out in Peru where 47.4% and 19.1% of the participants were overweight and obese respectively [ 39 ]; in Mexico, there is a record of 45% obesity in rural areas and 48% in urban areas [ 36 ], and in Venezuela it was evidenced that 60% of both populations are obese and overweight [ 40 ]. This variable is highly influenced by the lifestyle and customs of the two populations.…”
Section: Discussionsupporting
confidence: 88%
“…The distribution of drug use for arterial hypertension (HT) shows that the proportion of individuals with HT is higher in the urban population than in the rural communities, which coincides with studies carried out in Peru where the prevalence of HT was 18.6% in urban areas and 3.9% in rural areas [ 51 ]. The Peruvian jungle shows that in urban areas the prevalence of HT is 18.4% and in rural areas 6% [ 39 ], and Mexico reports a prevalence of 36% in urban areas and 18% in rural areas [ 36 ]. In Colombia, the report of the urban area by sex reports that in men the prevalence of HT is 37.3% while in women it is 28% [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al mismo tiempo, los fumadores presentan el doble de probabilidad de padecer HTA.11 Por otro lado, Tridade, et al, 16 y Sánchez, et al, 14 señalan que existe una asociación estadísticamente significativa entre el tabaquismo y la HTA. Por el contrario, Martínez, et al, 17 no encontró relación estadística significativa.…”
Section: Discussionunclassified
“…Las enfermedades cardiovasculares (ECV) son un trastorno crónico que se desarrolla de forma insidiosa, progresando incluso cuando no aparecen síntomas y/o signos, elevando más el grado de discapacidad al momento del diagnóstico1, se estima que en las próximas décadas la pérdida total de años de vida ajustados por discapacidad (AVAD) aumentaría de 85 millones en 1990 a 150 millones en 2020 2,3 y, por tanto, continuaría siendo la causa más importante de pérdida de productividad. La ECV está fuertemente relacionada con el estilo de vida, especialmente con el consumo de tabaco, los hábitos alimentarios poco saludables, la inactividad física y el estrés psicosocial 4,5 .…”
Section: Introductionunclassified